Structural Analysis and Design of Steel Structures Using Tekla Structural Designer: A Case Study in Banyuwangi - Bagas Rahmandita Subchan; Dwi Nurtanto; Syamsul Arifin; Setiyo F. Yanuar; Imam Junaidi; Slamet R. B. Prasetyo; Dian W. K. Novanto; Rino D. Saidi; Tedy Pranadiarso (Politeknik Negeri Lhokseumawe, 2026)
The increasing demand for efficient and reliable structural design in modern construction necessitates the integration of advanced computational tools within engineering workflows. This study investigates the structural analysis and design of a steel building using Tekla Structural Designer through a case study located in Banyuwangi.An integrated digital workflow encompassing three-dimensional modeling, load definition, structural analysis, and member design verification was implemented in accordance with relevant structural design standards. The applied loading scenarios include gravity loads and lateral loads representing realistic environmental conditions. Structural responses were evaluated in terms of internal forces, displacements, and utilization ratios.The results demonstrate that the structural system exhibits behavior consistent with theoretical expectations of steel moment-resisting frames. Maximum bending moments were observed at beam mid-spans, while axial forces accumulated in lower-level columns. Structural displacements remained within serviceability limits, confirming adequate stiffness. Design verification indicated that all members satisfied strength and stability requirements after iterative optimization.This study confirms that integrated structural design platforms significantly enhance efficiency and accuracy in engineering practice. Furthermore, the findings highlight the importance of combining computational tools with engineering judgment to ensure reliable and practical design outcomes. The research contributes to the growing body of knowledge on digital structural engineering and its application in real-world design scenarios.